2015
DOI: 10.1002/dc.23330
|View full text |Cite
|
Sign up to set email alerts
|

Expression, correlation, and prognostic value of TRAF2 and TRAF4 expression in malignant plural effusion cells in human breast cancer

Abstract: TRAF2 and nuclear TRAF4 expression in malignant pleural effusion cells may represent potential prognostic factors and biomarkers of invasion and metastasis in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…TRAF2 overexpression has been documented in tumor samples from certain types of cancer such as human pancreatic cancer, breast cancer and gastric cancer, and is associated with cancer progression, metastasis, and shorter patient survival [23, 25, 26]. The current study continues our previous exploration of the critical role of TRAF2-dependent enhancement of cancer cell invasion and metastasis induced by DR5 suppression [11] to further understand the mechanism by which TRAF2 is activated during DR5 suppression-induced promotion of cancer cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…TRAF2 overexpression has been documented in tumor samples from certain types of cancer such as human pancreatic cancer, breast cancer and gastric cancer, and is associated with cancer progression, metastasis, and shorter patient survival [23, 25, 26]. The current study continues our previous exploration of the critical role of TRAF2-dependent enhancement of cancer cell invasion and metastasis induced by DR5 suppression [11] to further understand the mechanism by which TRAF2 is activated during DR5 suppression-induced promotion of cancer cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It was documented TRAF2 plays vital roles in regulating immunity response, embryonic development, and stress response. TRAF2 expression has been reported to be upregulated in breast cancer [ 25 ]. Zhao et al [ 25 ] found that TRAF2 expression was upregulated in primary tumor and metastatic lymph nodes compared with normal breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“…TRAF2 expression has been reported to be upregulated in breast cancer [ 25 ]. Zhao et al [ 25 ] found that TRAF2 expression was upregulated in primary tumor and metastatic lymph nodes compared with normal breast tissues. Different biomarkers of prostate cancer have recently been identified [ 35 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations